Virtual Reality in Design Processes: - a literature review of benefits, challenges, and potentials - Strand, Ingri (FormAkademisk, 2020)
Virtual Reality (VR) opens new possibilities in the fields of architecture, design and engineering. If combined with Building Information Modelling (BIM) or simpler 3D models, it could be possible to walk into buildings not yet built or to examine designed objects in three dimensions before they are made. This literature review examines studies in which VR was used in architecture, design and engineering as part of design processes. The review highlights promising benefits, such as increased understanding of complex issues concerning design tasks, size and dimensions. At the same time, several challenges are revealed, such as the inability of VR-systems to offer satisfactory functionalities for sketching and designing. Finally, the author discusses how VR can be implemented in relevant subjects in lower and upper secondary school.